Outcome and complications in dogs with appendicular primary bone tumors treated with stereotactic radiotherapy and concurrent surgical stabilization. Issue 6 (6th May 2017) - Boston, Sarah E.; Vinayak, Arathi; Lu, Xiaomin; Larue, Susan; Bacon, Nicholas J.; Bleedorn, Jason A.; Souza, Carlos H. M.; Ehrhart, Nicole P.
Abstract: Objective: To document the outcome of dogs with appendicular primary bone tumors treated with stereotactic radiotherapy (SRT) and concurrent stabilization. Study design: Multi‐institutional retrospective case series. Animals: Eighteen dogs with presumptive or definitive diagnosis of appendicular osteosarcoma. Methods: Medical records of dogs with appendicular primary bone tumors treated with SRT and stabilization were reviewed for signalment, preoperative staging and diagnostics, radiation dose, stabilization method, and outcome. Results: The distal radius was affected in 13/18 cases. Osteosarcoma or sarcoma was confirmed cytologically or histologically in 15/18 cases. Seven dogs were diagnosed with a pathological fracture at the time of treatment, and 11 were considered at high risk for pathological fracture. Dogs received a single dose (n = 5) or 3 doses (n = 13) of SRT. Surgical stabilization was performed under the same anesthetic event as the final dose of SRT in 10 dogs. Stabilization was achieved with a bone plate (n = 15) or interlocking nail (n = 3). Seventeen dogs received adjuvant chemotherapy. Complications occurred in 16/17 dogs, 15/17 of those being considered major complications. Four dogs experienced more than one complication. Infection was the most common complication, diagnosed in 15/17 cases, and considered as a major complication in 13/15 cases. Postoperative fracture was recorded as a major complication in 3 cases. Nine dogs were amputated at a median of 152 days. The median survival time was 344 days. Conclusion: Treatment of bone tumors with SRT and concurrent stabilization was associated with a prohibitively high complication rate in dogs. Alternative methods for limb salvage should be considered for dogs at risk for pathologic fracture.